Energy Consumption and Stock Market Relationship: Evidence from Turkey - Ersoy, Ersan; Unlu, Ulas (International Journal of Energy Economics and Policy, 2013)
A large number of studies on the relationship between financial indicators and macroeconomic variables such as economic growth and energy as a result of the increase in the energy prices and their volatility in recent years have emerged. The aim of this study, apart from the other studies in the area, is to investigate the interaction between energy consumption and stock exchange index in Turkey. Ceteris paribus, economic growth with the increase of energy consumption, the growth of the economy impact will also affect the stock exchange which is accepted as the barometer of the economy (vice versa). The interaction between the BIST National 100 index, BIST National Industrial Index and energy consumption is investigated by Johansen Cointegration Test, Granger Causality Test tests based on VAR for the period of 1995-2011. Unidirectional causality relationship is detected from BIST 100 Index and BIST Industrial Index towards energy consumption. Keywords: Energy Consumption; Stock Market; BIST 100 Index; Cointegration; Causality JEL Classifications: E44; O4; Q4